Naval Diplomacy to Enhance Indonesia’s Maritime Security - Irwanto, Bambang (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
This study examines Indonesia’s role and contributions to the Maritime Task Force (MTF) of the United Nations Interim Force in Lebanon (UNIFIL), addressing the research question: How does Indonesia’s participation in the UNIFIL MTF contribute to its diplomatic standing and international peacekeeping efforts? While the role of naval diplomacy in international politics has been widely studied, limited research focuses on non-aligned nations, such as Indonesia, in multinational peacekeeping operations. This study aims to address this gap by analyzing Indonesia’s maritime diplomacy strategies and their implementation within UNIFIL’s peacekeeping mandate. Using a qualitative approach and the Miles and Huberman model, the research delves into Indonesia’s historical involvement in the MTF, its operational challenges, and its cooperation with the Lebanese Armed Forces (LAF). Challenges include coordinating with diverse international actors and achieving peacekeeping objectives in a conflict-prone region. The findings underscore the significance of maritime diplomacy as a critical tool for Indonesia’s foreign policy, demonstrating how its naval forces enhance regional stability and contribute to international security. Indonesia’s proactive role in the MTF highlights its commitment to global peace and security, strengthening its standing as a responsible international actor. In conclusion, Indonesia’s maritime diplomacy not only projects power but also fosters collaborative relationships that advance global peacekeeping efforts and position the nation as a key contributor to international stability.